Adjoint Method Shape Optimization of a Vertical Axis Wind Turbine - Van Stratan, G.S.M.; Roy, Sukanta; Vincent Lee, C.C.; Ke San, Y. (2024)
This study demonstrates the efficacy of the adjoint method to optimize a VAWT blade. A symmetrical blade NACA0018 was chosen as the starting geometry and the adjoint method was applied through 2D CFD simulation to obtain a optimized blade. The 2D adjoint optimization scheme was found to produce a strong candidate blade which improves the average single blade moment coefficient by over 30%. A 3D analysis was then conducted, and the candidate blade was compared against the baseline NACA0018 blade and an unsymmetrical blade S1046 blade. The results showed the candidate blade performed much better than the NACA0018 blade by 20.42% as well as the S1046 blade by 15.18%. These results indicate the adjoint method is a suitable optimization code to aerodynamically optimize and improve the VAWT turbine.